1976
DOI: 10.2134/agronj1976.00021962006800030008x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Element Accumulation by two Single‐cross Corn Hybrids as Affected by Copper in Solution1

Abstract: Increased use of land for “disposal” of industrial wastes and animal wastes such as poultry and swine manure from flocks and herds fed high levels of trace elements will require soil monitoring methods to maintain safe levels of these elements with respect to both crop production and the food chain. The objectives of this investigation were to: 1) measure Cu ion potentials, pCu, associated with minimum and maximum Cu ion activities for growth of corn (Zea mays L.) seedlings; 2) evaluate the influence of the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Applications of the high levels of Cu as either Cu rich manure or CUSO4 increased the DTPA extractable Cu in the three soils ( ship may reflect Cu uptake by roots with a low amount of Cu translocation from roots to shoots (1,11,12).…”
Section: Resultsmentioning
confidence: 95%
“…Applications of the high levels of Cu as either Cu rich manure or CUSO4 increased the DTPA extractable Cu in the three soils ( ship may reflect Cu uptake by roots with a low amount of Cu translocation from roots to shoots (1,11,12).…”
Section: Resultsmentioning
confidence: 95%
“…However, Romheld (1987) found that intact Fe-mugineic acid was accumulated by barley. By implication, Zn-and Cu-mugineic acid are also absorbed, and mugineic acid competition with DTPA for Zn or Cu was probably the characteristic being measured by Halvorson and Lindsay (1977) and Dragun et al (1976).…”
Section: 43mentioning
confidence: 99%
“…This should allow an estimation of the pCu 2+ , pMn 2+ , pZn 2 *, etc., at which soybeans can no longer remove these elements from nutrient solutions. Halvorson and Lindsay (1977) estimated the minimum pZn 2+ which allowed corn to obtain Zn was 10.6, and Dragun et al (1976) estimated the Tn-irnmim pCu 2+ from which corn could obtain adequate Cu was 13. It is now clear these papers probably relate only to Strategy-2 species where the competition is between the synthetic chelator and phytosiderophores such as mugineic acid.…”
Section: 43mentioning
confidence: 99%
“…An increase in phytotoxic response of corn (i.e. depression of root and shoot growth) corresponding to an increase in Cu content of plants, was observed by Dragun et al (16), only when plants were grown in Cu solutions, which were in equilibrium with soil solids, with concentrations greater than 1.26 mmol m" 3 .…”
Section: Resultsmentioning
confidence: 80%
“…Stunting of com plant growth upon exposure to Cu has been observed previously. Laboratory studies conducted by Dragun et al (16) revealed that corn plants grown in 10 mmol m~3 CuS0 4 solutions, in equilibrium with soil solids, resulted in a substantial decrease in height for plants after 4 wk compared to corn plants grown in solutions with Cu concentrations less than 10 mmol m~3. A far less dramatic decrease in plant height was observed for corn grown in 2.5 mmol m~3 Cu solution.…”
Section: Resultsmentioning
confidence: 99%